Pengaruh Lingkungan Kerja, Kesungguhan Kerja, Semangat Kerja Terhadap Kepuasan Kerja Karyawan PT Bromo Falcata Indonesia Kabupaten Probolinggo - Nur Diana Dewi; R Abdul Haris; Umi Rahma Dhany (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
The factory company PT Bromo Falcata Indonesia is engaged in barecore production with the location of activities being at Jalan Brantas km 1, Pilang sub-district, Kademangan sub-district, Probolinggo Regency. The independent variable consists of the work environment, work sincerity, and work enthusiasm while the dependent variable is job satisfaction. The population in this study is the entire workforce at PT Bromo Falcata Indonesia. The sampling technique in this study used a non-probability sampling technique, namely saturated sampling. Saturated sampling is a sampling technique when all members of the population are used as samples. The sample in this study is all workers at PT. Bromo Falcata Indonesia Probolinggo with 30 workers. Sources of data used in this study are primary data and secondary data. Processed using data analysis in the form of validity and reliability tests, classical assumption tests (normality test, heteroscedasticity test, multicollinearity test), multiple linear regression analysis, coefficient of determination, hypothesis testing (t test). The results of this study indicate that: work environment, work seriousness, work enthusiasm and significant effect on employee job satisfaction at PT Bromo Falcata Indonesia, Probolinggo Regency